Letter to the Editor Regarding the Article: "Inappropriate Prescribing to Elderly Patients in an Internal Medicine Ward" - Simões, Pedro Augusto Gomes Rodrigues Marques (2019)
Dear Editor, We read with interest an article about inappropriate prescribing to elderly patients in an internal medicine ward and a letter to the editor regarding the same paper. We developed a similar study in the Portuguese primary care setting with a nation-wide representative sample of 757 elderly patients in accordance to its distribution in Portuguese health regions and we found that 77% of them were on ≥ 5 medications (with a mean of 8.2) and that 68% had at least one potentially inappropriate medication according the to 2015 Beers Criteria (with a mean of 1.72). The most common potentially inappropriate pharmacological classes were proton pump inhibitors (45.6%), non-steroid anti-inﬂammatory agents (34.5%) and benzodiazepines (27.3%). As such, we were also surprised with the low proportion of inappropriate prescribing at admission and at discharge reported in the study. One of the explanations, that was already reported, is the restricted number of pharmacologica classes used. This does raise many questions. Are we managing the various problems of our population in the best way? Is it necessary to rethink the polypharmacy cut-off since with the aging of the population there is an increase in the number of chronic diseases and consequently an increase in the number of drugs necessary to control them? Do we have to practice according to the guidelines or according to our clinical judgement of pathophysiology? Does this defnition of fve drugs for polypharmacy put people at a higher risk of undermedication, instead of overmedication?5 Shouldn’t we think of a new defnition for polypharmacy that isn’t the same for all people, but which takes into account the burden of disease that it is subject to? E.g. does it make sense to use the same polypharmacy cut-off for a healthy individual and a post-myocardial infarction patient? We consider this issue as fundamental, since as already mentioned the management of multimorbidity and polypharmacy (more specifcally of potentially inappropriate medication) are essential pillars in the provision of health care nowadays, both in primary and secondary care. So this raises the question of time since, in medical education, when should this topic be addressed and by whom? It is also important to analyze if there are differences between the work at the different health care levels regarding the management of multimorbidity, polymedication and potentially inappropriate medication. Are we all working towards the same goal?